2005
DOI: 10.1007/s00018-005-5200-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic distribution, functional epitopes and evolution of the CSαβ superfamily

Abstract: A superfamily of proteins often conserves a common structural scaffold but develops diverse biochemical and biological functions during evolution. The understanding of evolutionary mechanisms responsible for this diversity is of fundamental importance not only in structural genomics but also in nature-guided drug design. A superfamily of peptides with a conserved CSalphabeta structural motif provides a considerably intriguing example to approach such an issue. The peptides from this superfamily have wide origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 71 publications
2
129
0
Order By: Relevance
“…Experimental deletion of the NC-domain of a scorpion toxin resulted in antifungal ability of the toxin 25 , whereas the addition of the NC-domain of a toxin on the drosomycin scaffold led to a neurotoxin targeting rat sodium channels 26 . These data provide convincing functional evidence in favour of evolutionary link between drosomycins and scorpion sodium channel toxins, and present an example of divergent evolution occurring in a specific arthropod lineage, in which a DTAFP evolved into a neurotoxin [24][25][26] . The insertion of a small fragment, as the N-turn of the scorpion toxins, in the N-terminal region of a DTAFP is also seen in mehamycin (Fig.…”
Section: Restricted Distribution Ofmentioning
confidence: 57%
See 2 more Smart Citations
“…Experimental deletion of the NC-domain of a scorpion toxin resulted in antifungal ability of the toxin 25 , whereas the addition of the NC-domain of a toxin on the drosomycin scaffold led to a neurotoxin targeting rat sodium channels 26 . These data provide convincing functional evidence in favour of evolutionary link between drosomycins and scorpion sodium channel toxins, and present an example of divergent evolution occurring in a specific arthropod lineage, in which a DTAFP evolved into a neurotoxin [24][25][26] . The insertion of a small fragment, as the N-turn of the scorpion toxins, in the N-terminal region of a DTAFP is also seen in mehamycin (Fig.…”
Section: Restricted Distribution Ofmentioning
confidence: 57%
“…Similarly, drosomycin has been found to gain ability in interacting with the fly voltage-gated sodium channel, possibly acting as a neuropeptide 25 . In C. remanei, cremycin-15 has evolved antibacterial activity described here, while scorpion venom-derived DTAFPs have switched their targets from fungi to animal sodium channels [24][25][26] . All these observations suggest that the gene can be fixed only in organisms where it developed important functions following gene duplication and speciation.…”
Section: Mvksyrsvfllvcvtflvivsspkntava--------dklig---s-cvwgavnytsdcnmentioning
confidence: 88%
See 1 more Smart Citation
“…Due to their direct interaction with altered/new pathogens, AMPs exhibit an extraordinary diversity in their biochemical and biological functions. It has been reported that positive Darwinian selection was the major driving force in the generation of diverse AMPs [47].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [47] also reported that many members of the CS-ab superfamily exhibited molecular diversity and diverse biological functions, and suggested that positive Darwinian selection is the major driving force in generating such diversity. The direct involvement of these peptides with the altered pathogens in a changing environment is probably the cause of such adaptive molecular evolution of these AMPs [25].…”
Section: Discussionmentioning
confidence: 99%